A A Systemic Lupus Erythematosus Accompanied with Myelodysplastic Syndrome,Grave’s Disease, and Sub-Acute Subdural Hemorrhage: A Case Report - I Nyoman Suarjana (Indonesian Journal of Rheumatology, 2022)
Background: The systemic lupus erythematosus (SLE) is a disease ofautoimmune etiology affecting multiple systems, involving most commonlyfemales of the reproductive age group and different clinical manifestationsin each individual. Case presentation: A 23-year-old female patient withsystemic lupus erythematosus (SLE) presented with myelodysplasticsyndrome (MDS), Grave’s disease, and sub-acute subdural hemorrhage(SDH). She had chief complaints of severe headache and gum bleeding. Threeweeks earlier, the patient experienced a head injury. SLE was diagnosed onbiological and immunological clinical ACR criteria and the patient never hada therapy before. Bone marrow aspiration (BMA) test was performed withMDS result. Thyroid function test was performed with the result of decreasedThyroid Stimulating Hormone (TSH) and increased FT4 with diffusedenlargement of thyroid gland. Brain CT Scan resulted in sub-acute SDH withmidline shift of 1.13 cm to the left. The patient underwent subdural drainagewith local anesthesia and received steroid, azathioprine, thiamazole andnon- selective beta-blocker. She was hospitalized for 21 days and wasdischarged with good condition. Conclusion: Further investigation of thepatient is needed to fully understand the correlation between MDS, SubduralHemorrhage and Grave’s Disease in associated with SLE.